Potential of Prosopis pallida and Prosopis juliflora for Bioethanol production - Purohit, Rekha; Patel, Beena; Harsh, L.N (Current Botany, 2013)
Prosopis pallida and Prosopis juliflora were collected from different parts of Rajasthan. Mesocarp of Prosopis pods was fermented. Initial sugar concentration 13% and 40% was reduced resulting into 6.14% and 18.89% of alcohol production in P. juliflora and P. pallida respectively. Therefore this plant has high potential for making the biothanol in arid and semiarid reigons of India. Biofuels are being increasingly seen as potential alternatives to the liquid fossil fules.